2020
DOI: 10.1136/neurintsurg-2020-016783
|View full text |Cite
|
Sign up to set email alerts
|

Toward a more inclusive paradigm: thrombectomy for stroke patients with pre-existing disabilities

Abstract: BackgroundPersons with pre-existing disabilities represent over one-third of acute stroke presentations, but account for a far smaller proportion of those receiving endovascular thrombectomy (EVT) and thrombolysis. This is despite existing ethical, economic, legal, and social directives to maximize equity for this vulnerable population. We sought to determine associations between baseline modified Rankin Scale (mRS) and outcomes after EVT.MethodsIndividuals who underwent EVT were identified from a prospectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 32 publications
1
31
0
Order By: Relevance
“…Since pre-stroke disability will continue to rise in the coming years (7), the potential impact of ET on outcome in patients with prior disabilities has received increased attention. In fact, several recent case series as well as an analysis of the MR Clean Registry have revealed favorable functional and procedural outcome rates after ET in patients with prior disabilities compared to those without pre-stroke disability (8)(9)(10)(11)), yet all of these studies lacked a control group, such that the true treatment effect of ET in pre-stroke disabled patients is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Since pre-stroke disability will continue to rise in the coming years (7), the potential impact of ET on outcome in patients with prior disabilities has received increased attention. In fact, several recent case series as well as an analysis of the MR Clean Registry have revealed favorable functional and procedural outcome rates after ET in patients with prior disabilities compared to those without pre-stroke disability (8)(9)(10)(11)), yet all of these studies lacked a control group, such that the true treatment effect of ET in pre-stroke disabled patients is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Age and sex were recorded at the time of enrollment (12). The presentation National Institutes of Health Stroke Scale (NIHSS) was determined at clinical examination by certified neurologists to measure clinical stroke severity (13). The time from last seen well and stroke onset was documented.…”
mentioning
confidence: 99%
“…[5][6][7] Consequently, the recently updated guidelines from the American Stroke Association/American Heart Association have suggested that only patients with pre-stroke mRS 0-2 should undergo MT. 8 Nevertheless, recent studies have reported no increase in mRS status in 20.7% of patients with premorbid mRS 3 9 , 26.7% of patients with mRS 2-3 10 and 24% of patients with mRS 2-4 11 The aim of this study was to examine whether the functional outcome of patients with pre-stroke mRS 3 undergoing MT at our stroke centre compared favourably to those previously reported. We also sought to analyse the financial implications of performing MT as measured by change in accommodation costs.…”
Section: Introductionmentioning
confidence: 83%